Assessment of groundwater quality for irrigation purpose using irrigation water quality index (IWQI) - Al-Aizari, Hefdhallah S.; Aslaou, Fatima; Mohsen, Osan; Al-Aizari, Ali R.; Al-Odayni, Abdel-Basit; Abduh, Naaser A. Y.; Al-Aizari, Abdul-Jaleel M.; Abo Taleb, Eman (Journal of Environmental Engineering and Landscape Management, 2024)
Groundwater represents an important natural resource for sustaining life. This study was conducted to evaluate groundwater in the Doukkala region in Morocco, using the Irrigation Water Quality Index (IWQI) and uses Inverse Distance Weighting (IDW) in GIS was to show the spatial distribution of water quality parameters. It collected 97 of samples from groundwater and were estimated the sodium concentration (Na%), and sodium absorption rate (SAR), Also, Residual sodium carbonate (RSC), Kelly index (KI), magnesium content (MR), salinity potential (PS), and permeability index (PI). According to the distribution map of the Irrigation Water Quality Index (IWQI) for the study area, about 22.7% of samples fall into the severe restriction (SR) category, which can be used to irrigate plants with high salinity tolerance, 34.02 of samples fall under the high restriction (HR) category, 23.7% of samples fall into the moderate restrictions (MR) category, 17.52% of samples fall under the low restriction (LR) category, and 2.06% of samples fall under the no restriction (NR) category. The results of (IWQI) indicated that the groundwater quality in the study area is mostly suitable for irrigation purposes.